The solution is
![x = (-29)/(13), y = (69)/(26)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r1jhguh4rzzxtazvulei0lc9oyk5t3zlds.png)
Solution:
Given system of equations are:
4x + 6y = 7 --------- eqn 1
3x - 2y = -12 -------- eqn 2
Let us solve the system of equations by elimination method
Multiply eqn 2 by 3
9x - 6y = -36 ----- eqn 3
Add eqn 1 and eqn 3
4x + 6y = 7
9x - 6y = -36
( + ) --------------
13x = -29
![x = (-29)/(13)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8dpfzpdw9pptm9tgwu4swimycfdy4p48t6.png)
Substitute
in eqn 1
![4( (-29)/(13)) + 6y = 7\\\\6y = 7 + (4 * 29)/(13)\\\\6y = (207)/(13)\\\\y = (69)/(26)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vl8v6i56izqnj3fgmax559440q1iorvc0g.png)
Thus the solution is
![x = (-29)/(13), y = (69)/(26)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r1jhguh4rzzxtazvulei0lc9oyk5t3zlds.png)